Uji efektivitas antidiare ekstrak etanol biji asam Jawa (Tamarindus indica L.) terhadap mencit jantan dengan metode transit intestinal - Simanjuntak, Nerly Juli Pranita; Neswita, Elfia; Lubis, Asyrun Alkhairi; Yunus, Muhammad (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Tamarindus indica is a member of the Fabaceae plant family, often used as a food source and traditional medicine. For generations, tamarind has often been used in medicine. One part of this plant that is often used is the seeds, which treat various conditions such as asthma, bronchitis, leprosy, tuberculosis, wounds, stomach problems, diarrhea, dysentery, vertigo, and diabetes. The active components of tamarind seeds include tannin compounds, fatty acids, flavonoids, saponins, alkaloids, and glycosides. This study used the intestinal transit method to examine the antidiarrheal effect of ethanol extract from tamarind seeds on male mice. This research method uses the intestinal transit method, namely comparing the length of the intestine through which the marker passes. The results of the observation of the antidiarrheal effect of the ethanol extract of tamarind seeds at a dose of 50 mg/kg bw gave the weakest antidiarrheal effect. The 450 mg/kg bw dose gave the most substantial antidiarrheal effect. Increasing the tamarind seed ethanol extract dose increased the antidiarrheal effect. The results of statistical analysis showed that administration of 2% tamarind seed ethanol extract suspension at a dose of 150 mg/kg bw and 450 mg/kg bw to male mice showed a practical antidiarrheal effect because it was not significantly different from loperamide 0.52 mg/kg bw which showed an impact. Antidiarrheal in Duncan's mean difference test (P > 0.05). The conclusion is that the ethanol extract of tamarind seeds has an antidiarrheal effect when given to male mice induced with oleum ricini using the small intestine passage method.